KUALITAS VISUM ET REPERTUM PERLUKAAN DI RSUD DR.RM.PRATOMO BAGAN SIAPI-API PERIODE 1 JANUARI 2009 - 31 DESEMBER 2013 - Ramadhan, Fadlan Tri; Afandi, Dedi; Mursali, Laode Burhanuddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTThe most frequent Visum et repertum (VeR) requested by investigators is VeR of injury. It is because 50-70% of cases that come to the Emergency Unit are injury cases. A good quality of VeR is required in view of its important role in litigation of a criminal offense. This study was aimed to understand the quality of VeR of injury in Dr.RM.Pratomo General Hospital of Bagan Siapi-api during 1 January 2009-31 December 2013. The research was an observational study using descriptive retrospective design. This study used Herkutanto’s scoring method towards 13 VeR substances. Samples of this study were all data of VeR of injury that had fulfilled inclusion criteria. The total of samples were 48 samples of VeR. This study suggested that the highest number of living victims of injury cases was 29 victims (60,4%) in age group 22-40 years old with the most frequent sex was male as many as 36 victims (75%). The most frequent violence was sharp violence as many as 28 cases (58,3%) with the most frequent age group was 22-40 years old. The quality of VeR in preface was 71% (medium), in body part was 51,56% (medium) and in conclusion was 28,12% (poor). In general, quality of VeR of injury in RSUD Dr.RM.Pratomo General Hospital of Bagan Siapi-api during 1 january 2009-31 december 2013 was 39,46% that could be categorized as poor quality.Keywords: Visum et Repertum, injury, quality of VeR of injury